2022
DOI: 10.3389/fncom.2022.932615
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Location of Axonal Activation by a Miniature Magnetic Coil

Abstract: Magnetic stimulation for neural activation is widely used in clinical and lab research. In comparison to electric stimulation using an implanted electrode, stimulation with a large magnetic coil is associated with poor spatial specificity and incapability to stimulate deep brain structures. Recent developments in micromagnetic stimulation (μMS) technology mitigates some of these shortcomings. The sub-millimeter coils can be covered with soft, biocompatible material, and chronically implanted. They can provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…Previous studies suggested that axonal activation is ineffective when the electric field component is perpendicular to the axon direction (Amassian et al, 1989;Basser and Roth, 2000;Golestanirad et al, 2018). Thus, the activating function (AF) is the electric field gradient along the direction of the axon, which is also known as the driving function for the activation of the axon (Rattay, 1989;Ye, 2022). The AF [V/m 2 ] when the nerve axon is parallel to the x-axis is as follows,…”
Section: Electromagnetic Simulationmentioning
confidence: 99%
“…Previous studies suggested that axonal activation is ineffective when the electric field component is perpendicular to the axon direction (Amassian et al, 1989;Basser and Roth, 2000;Golestanirad et al, 2018). Thus, the activating function (AF) is the electric field gradient along the direction of the axon, which is also known as the driving function for the activation of the axon (Rattay, 1989;Ye, 2022). The AF [V/m 2 ] when the nerve axon is parallel to the x-axis is as follows,…”
Section: Electromagnetic Simulationmentioning
confidence: 99%
“…This paper will examine the consistency of axonal activation by a figure-eight micro-coil, and investigate the underlying ion channel mechanisms using combined activating function analysis and NEURON modeling. We will compare these results from our recent analysis on a single, circular micro-coil ( Ye, 2022 ). This work provides valuable insights to the further development of μMS technology for focal and consistent neural stimulation.…”
Section: Introductionmentioning
confidence: 97%
“…This field gradient, or activating function, is directly related to the site of neural activation ( Rattay, 1986 ; Lee and Fried, 2017 ). Therefore, several research endeavors have computed the activating function for the single coil system to identify the site of neural activation ( Lee et al, 2016 ; Ye, 2022 ). We recently simulated axonal activation by a circular micro-coil using activating function analysis and NEURON simulation ( Ye, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations